PENCEGAHAN MENINGKATNYA KASUS BUNUH DIRI MAHASISWA: SEBUAH ALARM BAGI KAMPUS DAN MASYARAKAT - Naylla Rachma Edhisty; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to raise awareness and identify preventive measures in reducing suicides among university students, caused by academic pressure, mental disorders, and lack of social support. The research method used a literature review with an analysis of 13 relevant articles from journals accessed through Google Scholar, using the keywords